A study on perceived stress among new tertiary education institution students in Malaysia / Mohd Syafiq Abdul Rahman ... [et al.] - Abdul Rahman, Mohd Syafiq; Umar, Norazah; Libasin, Zuraira; Azudin, Ahmad Rashidi; Idris, Nur Azimah (Unit Penerbitan JSKM, 2021)
As the number of COVID-19 cases keep fluctuating, the Ministry of Higher Education in Malaysia had ordered all lessons should be conducted remotely in 2020 but exceptions were also given to certain needs. New first-year students were greatly affected as they did not get the chance to experience the university life. Thus, this study aims to analyse the perceived stress level among the first-year students due to remote teaching and learning. 272 students from 6 faculties and three different education levels namely pre-diploma, diploma, and degree from a tertiary education institution in Penang, Malaysia participated in this study. This study adopted a questionnaire by AlAteeq et al. (2020). The survey was developed using Google Form which later disseminated through WhatsApp and Telegram. The demographic and perceived stress data were analysed using frequencies and percentages of each item to see its trend and pattern. The conclusion was made based on the Perceived Stress Scale (PSS) by Cohen et al. (1983). The findings is alarming since 249 from 272 students (91.5%) were categorized in high stress level, followed by moderate stress (7.7%) and low stress (0.7%).